2010
DOI: 10.1001/jama.2010.39
|View full text |Cite
|
Sign up to set email alerts
|

Relation Between Kidney Function, Proteinuria, and Adverse Outcomes

Abstract: The risks of mortality, myocardial infarction, and progression to kidney failure associated with a given level of eGFR are independently increased in patients with higher levels of proteinuria.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

30
618
7
12

Year Published

2010
2010
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 915 publications
(682 citation statements)
references
References 26 publications
30
618
7
12
Order By: Relevance
“…This is particularly relevant, given the association between albuminuria and progression to kidney failure in other populations. 14 Despite a higher prevalence of heavy albuminuria among First Nations people, we did not find that the presence or severity of albuminuria conferred an additional risk to the development of kidney failure. Even among participants with no measure of albuminuria, risk of progression to kidney failure was similarly elevated for First Nations compared with non-First Nations participants within each category of estimated GFR.…”
Section: Discussioncontrasting
confidence: 74%
See 2 more Smart Citations
“…This is particularly relevant, given the association between albuminuria and progression to kidney failure in other populations. 14 Despite a higher prevalence of heavy albuminuria among First Nations people, we did not find that the presence or severity of albuminuria conferred an additional risk to the development of kidney failure. Even among participants with no measure of albuminuria, risk of progression to kidney failure was similarly elevated for First Nations compared with non-First Nations participants within each category of estimated GFR.…”
Section: Discussioncontrasting
confidence: 74%
“…We chose to use albuminuria measured by urine dipstick rather than urine albumin to creatinine ratio, because urine dipstick measurements are available for more people. Furthermore, our previous work has shown that albuminuria is an important determinant of clinical outcomes, including progression to kidney failure, whether assessed by urine dipstick or urine albumin to creatinine ratio, 14 supporting the validity of this measure.…”
Section: Classification Of Ethnicitymentioning
confidence: 64%
See 1 more Smart Citation
“…13,14 It is known that proteinuria is associated with the risk of cardiovascular disease. [15][16][17] Therefore, because of the antiproteinuric effect, benidipine would seem to be more advantageous than an L-type CCB, not only by slowing the progression of renal tissue injuries but also by reducing the incidence of cardiovascular events in patients with CKD. In terms of reducing proteinuria in diabetic and non-diabetic renal disease, ACE inhibitors and ARBs have been shown to be more effective than other classes of antihypertensive agents.…”
Section: Discussionmentioning
confidence: 99%
“…Not only is the presence of CKD a likely factor in accelerating development of coronary disease in these patients but it has also been associated with an increase in other risks including hemorrhagic complications, contrast nephropathy, re-stenosis, and death [10]. Thus, multiple studies now confirm that proteinuria is a graded risk factor for CVD independent of GFR, hypertension, and diabetes and that this risk extends down into ranges of albumin excretion generally considered "normal" [21,22]. Moreover, this increased CV risk has been well demonstrated in several studies where only dipsticks were used to screen for increased protein excretion [6,18,23].…”
Section: Proteinuria and CV Riskmentioning
confidence: 99%